Geographic Information System-Based Framework for Sustainable Small and Medium-Sized Enterprise Logistics Operations - Jonathan Agoo; Renz Joshua Lanuza; Jonathan Lee; Paul Anthony Rivera; Neil Oliver Velasco; Marielet Guillermo; Arvin Fernando (ISPRS International Journal of Geo-Information)
Dispatching goods is becoming more difficult to manage in the field of logistics due to the high demand for order shipments. This is related to the increasing popularity of the use of e-commerce platforms by consumers, where products are required to be delivered rather than being bought in physical stores. Dispatch management is one of the critical components in a supply chain since it covers the coordination of tasks among stakeholders from the warehouse to the consumer’s doorstep. In this study, the authors propose a framework leveraging geographic information to sustain logistics operations, specifically in terms of managing last-mile delivery and return trip orders. This includes scheduling, communications, and the inventorying of the shipment status of goods. A mobile application built on this framework was integrated with a waypoint order optimization algorithm considering an entire route that traverses all the required pick-up and delivery points. It was pilot tested with an actual dispatch operation of a logistics company, yielding decreases of 92% and 43% in the average turnaround time and carbon footprint per completed service request, respectively, a decrease of 57% in operations cost, and an increase of 72% in profit. With the adoption of this framework, this study aims to contribute to the overall efficiency and sustainability of logistics operations in a wider geographic range.